QUALITY MANAGEMENT AND THE ECONOMICS OF GREEN COFFEE HERMETIC STORAGE - Natalie K. Donovan; Kenneth A. Foster; Carlos Alberto Parra Salinas (International Journal of Food and Agricultural Economics, 2020)
Coffee (Coffea arabica L.) is an important agricultural product in Colombia accounting for 16 percent of agricultural GDP. Issues of high humidity in the Central Andean Mountain Range make managing post-harvest product quality a challenge. In fact, Colombian coffee farmers do not store coffee due to the climate and the lack of affordable storage technologies. This research analyzes the economic potential of hermetic storage of green coffee in the Central Andes region of Colombia. Seasonality in prices, the effectiveness of Purdue Improved Crop Storage (PICS) bags, and reuse of the bags lead to positive net economic benefits related to adopting this quality management approach. The estimated discounted net economic returns are between 1,480 COP ($0.50 USD) and 4,895 COP ($1.70 USD) per 50 kg bag over a three year expected life or approximately 329,327 COP ($113.50 USD) to 1,089,089 COP ($375.50 USD) for the average sized Colombian coffee farm’s total expected production.